2006
DOI: 10.1073/pnas.0604705103
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 inhibition transiently activates Src kinase and promotes Src-dependent Akt and Erk activation

Abstract: Hsp90 plays an essential role in maintaining stability and activity of its clients, including oncogenic signaling proteins that regulate key signal transduction nodes. Hsp90 inhibitors interfere with diverse signaling pathways by destabilizing and attenuating activity of such proteins, and thus they exhibit antitumor activity. However, Hsp90 inhibition has recently been reported to activate Akt and Erk and potentiate Akt activation induced by insulin-like growth factor 1 and insulin, raising the concern that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
112
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(132 citation statements)
references
References 38 publications
13
112
0
3
Order By: Relevance
“…S1B). The latency of Akt activation compared to activation of Src suggests that the former could be Src-dependent, as we previously reported in bladder and breast cancer cells (8). That the Src inhibitor PP1 fully blocked 17-AAG-induced Akt activation (Fig.…”
Section: -Aag Promotes Osteoclastogenesis Through Src Kinase Activasupporting
confidence: 48%
See 2 more Smart Citations
“…S1B). The latency of Akt activation compared to activation of Src suggests that the former could be Src-dependent, as we previously reported in bladder and breast cancer cells (8). That the Src inhibitor PP1 fully blocked 17-AAG-induced Akt activation (Fig.…”
Section: -Aag Promotes Osteoclastogenesis Through Src Kinase Activasupporting
confidence: 48%
“…This phenomenon has also been observed for the RNA-dependent serine-threonine kinases PKR and Raf-1 (9,10) and for the tyrosine kinase ErbB2 (11). Such transient activation, although short-lived itself, can in certain cases propagate a downstream signaling cascade of much longer duration (8).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Hsp90 is thought to direct the folding of Src kinases into the inactive conformation, which prevents their degradation (Xu and Lindquist, 1993;Xu et al, 1999). Interestingly, inhibition of Hsp90 with GA rapidly disrupts Src association with Hsp90, leading to transient activation of c-Src (Koga et al, 2006). We now demonstrated that Hsp90 is also a bona fide Src substrate in response to VEGFR-2 activation, which results in activation of Hsp90, suggesting a reciprocal influence between the two proteins that regulates both their activity in endothelial cells.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have shown that HSP90 inhibition reduces activation of Akt and ERK, which are downstream of multiple clients of HSP90, contributes to induction of apoptosis (24,47,48). In particular, Akt itself is known to be a HSP90 client protein (49).…”
Section: Discussionmentioning
confidence: 99%